Advantage Of Physical Methods Of Treatment Of Patients With Neurocirculatory Dystonia (Eurasian Medical Research Periodical, 2024)
The article presents questions devoted to modern aspects of the use of therapeutic physical factors in patients with neurocirculatory dystonia.